A conjugated porphyrin as a red-light sensitizer for near-infrared emission of ytterbium(iii) ion. (27th October 2020) - Balasooriya, Dinesh; Liu, Beibei; He, Hongshan; Sykes, Andew; May, P. Stanley
Abstract : A conjugated porphyrin with broader absorption in the visible region was synthesized for sensitizing the near-infrared emission of ytterbium(iii ) ions. Abstract : A conjugated porphyrin with broader absorption in the visible region was synthesized for sensitizing the near-infrared emission of ytterbium(iii ) ions. The 4-ethynylbenzoic acid was linked to the meso position of a 5, 15-dimesitylporphyrin resulting in a conjugated porphyrin, which has strong absorption in the visible region with an onset of up to 670 nm. After forming a complex with ytterbium(iii ) acetate and 1, 10-phenanthroline in sulfolane, the absorption edge shifted to ∼650 nm with a peak absorption at 615 nm. It was found the fluorescence from porphyrin in the visible region was almost diminished in the complex. Upon excitation at a wavelength above 600 nm, the complex showed characteristic emission at 980 nm from ytterbium(iii ) ions with a lifetime of 12.0 μs in dichloromethane. The NIR emission was also observed in DMSO/water (1 : 1) upon excitation at 633 nm, demonstrating its potential for biological applications.